SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PENGADAAN BUKU PERPUSTAKAAN MENGGUNAKAN METODE K-MEANS DAN ELECTRE - Arifin Tua Purba; Heru Sugara; Hengki Mangiring Parulian Simarmata; Doris Yolanda Saragih; Erikson Damanik (Politeknik Bisnis Indonesia, 2023)
This study aims to solve the problem of grouping books that are most often borrowed at the library and provide priority recommendations for procuring the right books. Currently the priority for procuring books at the Sekolah Tinggi Akuntansi dan Manajemen Indonesia (STAMI) Library is still done manually. To overcome this problem, two methods are used, namely the K-Means method which functions to group books based on the number of book titles and the ELECTRE method which is used to prioritize books to be purchased. The decision support system built using the ELECTRE method utilizes criteria consisting of the number of books borrowed, copies, book prices, and majors. The results of this study are a web-based decision support system consisting of 11 alternatives grouped, namely: Buku-013, Buku-063, Buku-072, Buku-074, Buku-075, Buku-076, Buku-084, Buku - 092, Book-102, Book-122, and Book-125. With this Decision Support System, the Library of the Indonesian College of Accounting and Management can easily prioritize procuring books in the library.